Efektivitas Bahan Ajar Digital Berbasis Konflik Kognitif Terintegrasi Augmented Reality dan Etnosains Nias untuk Meningkatkan Berpikir Kritis Pada Materi Usaha dan Energi - Elman Ikhtiar Ronaldo Waruwu; Fatni Mufit; Asrizal; Emiliannur (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effectiveness of digital learning materials based on cognitive conflict integrated with Augmented Reality (AR) and Nias ethnoscience in improving students' critical thinking skills in the material of work and energy. The method used was a quasi-experiment with a pretest-posttest control group design. The research sample consisted of two eleventh grade Physics classes at SMA Negeri 1 Gido selected through simple random sampling. The instrument used was an essay test to measure critical thinking skills. The results showed that the average posttest score of the experimental class (75.1) was higher than that of the control class (70.4). Hypothesis testing using Mann-Whitney U resulted in a significance value of 0.039, indicating a significant difference between the two groups. These findings indicate that the developed digital learning materials are effective in improving students' critical thinking skills. This effectiveness is supported by the integration of cognitive conflict that encourages conceptual reconstruction, the use of AR that visualizes abstract concepts, and ethnoscience that links learning to the local cultural context.